Business as unusual : managing commercial property in distress - Furfine, Craig ([London] : SAGE, 2016)
In January 2010, Benedict Clarke, general partner of a small real estate private equity venture, faced difficulty with one of his properties. When purchased in early 2007, Tulaberry Plaza was a thriving retail shopping center outside Orlando, Florida. The financial crisis and severe economic downturn forced Tulaberry's anchor tenant into bankruptcy and weakened the other tenants in the plaza. Clarke now faces pressures placed on him by his limited partners, who were shown rosy projections of the returns they would receive, and by his lender, who is presently taking most of the property's cash flow to satisfy required debt service. Clarke must devise a plan that presents the most logical and profitable way forward, while also justifying his actions to elicit the necessary support from his stakeholders.
Originally Published in: Furfine, C. (2014). Business as Unusual: Managing Commercial Property in Distress. 5-413-759. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 28, 2016).
Keywords: elektronické knihy; electronic books; Real estate management -- Case studies; Real estate management -- Finance -- Case studies